Altered ubiquitin signaling induces Alzheimer’s disease-like hallmarks in a three-dimensional human neural cell culture model - Maniv, Inbal; Sarji, Mahasen; Bdarneh, Anwar; Feldman, Alona; Ankawa, Roi; Koren, Elle; Magid-Gold, Inbar; Reis, Noa; Soteriou, Despina; Salomon-Zimri, Shiran; Lavy, Tali; Kesselman, Ellina; et al. (Nature communications, 2023)
Alzheimer’s disease (AD) is characterized by toxic protein accumulation in the brain. Ubiquitination is essential for protein clearance in cells, making altered ubiquitin signaling crucial in AD development. A defective variant, ubiquitin B + 1 (UBB +1 ), created by a non-hereditary RNA frameshift mutation, is found in all AD patient brains post-mortem. We now detect UBB +1 in human brains during early AD stages. Our study employs a 3D neural culture platform derived from human neural progenitors, demonstrating that UBB +1 alone induces extracellular amyloid-β (Aβ) deposits and insoluble hyperphosphorylated tau aggregates. UBB +1 competes with ubiquitin for binding to the deubiquitinating enzyme UCHL1, leading to elevated levels of amyloid precursor protein (APP), secreted Aβ peptides, and Aβ build-up. Crucially, silencing UBB +1 expression impedes the emergence of AD hallmarks in this model system. Our findings highlight the significance of ubiquitin signalling as a variable contributing to AD pathology and present a nonclinical platform for testing potential therapeutics. Using a 3-D neural platform, the authors show that a ubiquitin variant is sufficient to induce Alzheimer’s disease-like pathology in human neurons. Suppressing expression of this variant improved pathology in neurons carrying familial mutations.